Melanocytoma of the Optic Nerve Head, Thirty-Month Follow-Up. (2nd November 2015) - Eldaly, Hasan; Eldaly, Zeiad
Abstract: Introduction : Optic nerve head (ONH) melanocytoma is a benign pigmented tumor that is detected as a dark brown mass on or adjacent to the optic disc. Ultrasonography, optical coherence tomography (OCT), and fundus fluorescein angiography (FFA) can be used to differentiate it from other pigmented tumor as well as to monitor tumor growth. Visual field changes are variable in ONH melanocytoma. Usually, ONH melanocytoma has a stationary course with few cases of progressive growth or malignant transformation. Case Presentation : A 54-year-old female complained of blurring of vision. Best-corrected visual acuity (BCVA) was 0.9 in both eyes. On routine fundus examination, an elevated pigmented lesion was found, involving the optic nerve head of the left eye. B-scan ultrasound demonstrated a mass arising from ONH. FFA revealed blocked fluorescence corresponding to pigmented mass. HR-OCT scans showed a dome-shaped, elevated ONH lesion with highly reflective layer and optical shadowing behind it, obscuring most of the optic nerve head details. On regular follow-up for 30 months, the lesion had neither changed in its size nor affected the patient's visual acuity. Conclusion : ONH melanocytoma is a benign tumor with rare malignant transformation and visual impairment.